2001
DOI: 10.1021/la010529p
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Structural Studies of Triton X-100 Micelles in Ethylene Glycol−Water Mixed Solvents

Abstract: Micellar properties of p-tert-octyl-phenoxy (9.5) polyethylene ether (Triton X-100) in aqueous mixtures of ethylene glycol (EG) were determined using such techniques as surface tension, static and dynamic light scattering, and fluorescence spectroscopy. Thermodynamics of micellization was obtained from the temperature dependence of critical micelle concentration values. The differences in the Gibbs energies of micellization of Triton X-100 between water and binary solvent systems were calculated to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
126
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(144 citation statements)
references
References 56 publications
14
126
3
Order By: Relevance
“…An increase in the CMC with an increase in the EG concentration is also common for nonionic surfactants; however, for nonionic surfactant, the effect is more prominent than for an ionic one. Ruiz et al [58] found the CMC of an ethoxylated alkylphenol increased from 0.23 mmol dm -3 to *0.35 mmol dm -3 in 20% EG, at 298 K. Higher CMC value with increasing EG concentration is a consequence of increasing hydrophobicity, contributed by a structure breaking solute, herein EG oligomers. Water-glycol mixtures are better solvents for surfactant molecules than pure water.…”
Section: Critical Micelle Concentrationmentioning
confidence: 95%
“…An increase in the CMC with an increase in the EG concentration is also common for nonionic surfactants; however, for nonionic surfactant, the effect is more prominent than for an ionic one. Ruiz et al [58] found the CMC of an ethoxylated alkylphenol increased from 0.23 mmol dm -3 to *0.35 mmol dm -3 in 20% EG, at 298 K. Higher CMC value with increasing EG concentration is a consequence of increasing hydrophobicity, contributed by a structure breaking solute, herein EG oligomers. Water-glycol mixtures are better solvents for surfactant molecules than pure water.…”
Section: Critical Micelle Concentrationmentioning
confidence: 95%
“…The aggregation behavior of surfactants in nonaqueous polar solvents and aqueous-organic mixed solvents has been the subject of much attention in the past few years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). This interest is due to two reasons: (i) the necessity of elucidating the effects of solvent quality on the nature of self-assembly of 1 To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Such a combined structured phase also provides a complete hydrophobic environment for amphiphilic molecules as of surfactants to assemble in a similar way as they do in pure water. [11][12][13] Polyethylene oxide-polypropylene oxide-polyethylene oxide (PEO-PPO-PEO) copolymers exist in different states of aggregation in aqueous solution depending on relative block sizes, concentration, and temperature. The self-association behavior of these copolymers in water has attracted great attention.…”
Section: Introductionmentioning
confidence: 99%